Anodic Polymerization of Phenylphenols in Methyl Isobutyl Ketone and Mesityl Oxide: Incorporation of a Cavitand into the Layers Formed for Sensing Phenols in Organic Media - László Kiss; Zoltán Nagymihály; Péter Szabó; László Kollár; Sándor Kunsági-Máté (Molecules, 2022)
The electropolymerization of three phenylphenol isomers was studied in methyl isobutyl ketone and mesityl oxide, and the remarkable differences highlighted the importance of the carbon–carbon double bond in mesityl oxide. In the case of each substrate, a brownish deposit formed during the electrooxidation. The obvious difference between the polymers formed from the two solvents was recognized via voltammetric signal enhancement of 4-methoxyphenol and 4-chlorophenol, and it was only observed in the case of mesityl oxide. The experiments highlighted that incorporation of a cavitand with biphenyl groups on the upper rim of the polymers of phenylphenols improved the results to a small extent. The cavitand was, itself, electroactive without any fouling effect. As 2-phenylphenol is by far the cheapest of the three isomers, a cavitand was incorporated into its polymer, which was exploited to solve analytical problems while mesityl oxide was used as solvent. Useful quantifications were achieved in organic solvents; however, it failed under aqueous conditions due to the high hydrophobicity of the deposit. Application of differential pulse voltammetry for 4-methoxyphenol and 4-chlorophenol gave detection limits of 9.28 and 50.8 μM in acetonitrile, respectively. This procedure resulted in the immobilization of cavitand derivatives onto the electrode’s surface, and the layer formed offered selective sensing of phenols by electrochemical methods.